Comparison of Effectiveness of Modified Del Nido Vs Conventional Del Nido Cardioplegia in Cardiac Surgery - Rehan Shahid, Muhammad Ismael, Muhammad Mubashar Umair (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Myocardial protection during cardiac surgery is crucial to minimize ischemic injury and postoperative complications. Del Nido cardioplegia (DNC), originally developed for pediatric patients, has gained widespread use in adult cardiac surgery due to its long-acting myocardial arrest properties. However, its high crystalloid content raises concerns of hemodilution and myocardial edema. Modified Del Nido cardioplegia (MDN), with a reversed blood-to-crystalloid ratio (4:1), aims to overcome these limitations while maintaining adequate myocardial protection. Objective: This study compared the clinical effectiveness of Modified Del Nido versus Conventional Del Nido cardioplegia in adult cardiac surgery patients undergoing cardiopulmonary bypass (CPB). Methods: A prospective, cross-sectional, non-interventional study was conducted at the Punjab Institute of Cardiology, Lahore, including 102 patients aged 18–75 years undergoing elective on-pump cardiac surgery. Group A received conventional DNC (1:4 blood-to-crystalloid), and Group B received MDN (4:1 ratio). Primary endpoints included CK-MB, CPK, hemodilution, and inotropic support. Secondary endpoints were aortic cross-clamp time, CPB duration, and postoperative ventilation time. Statistical analysis was performed using SPSS v20, with significance set at p<0.05. Results: MDN cardioplegia demonstrated significantly lower CK-MB levels at 12 hours postoperatively (p<0.05), indicating reduced myocardial injury. Hemodilution and blood transfusion requirements were lower in the MDN group. ALT levels were slightly higher in MDN, while ionotropic support needs were lower in DNC (p<0.05*). Conclusion: Modified Del Nido cardioplegia provided superior myocardial protection and reduced hemodilution compared to Conventional Del Nido. Further multicenter prospective studies are warranted to validate these findings and assess long-term clinical outcomes. Keywords: Modified Del Nido cardioplegia, Conventional Del Nido cardioplegia, Myocardial protection, Cardiac surgery, Cardiopulmonary bypass